NLRX1 Deletion Increases Ischemia-Reperfusion Damage and Activates Glucose Metabolism in Mouse Heart - Zhang, Hong; Xiao, Yang; Nederlof, Rianne; Bakker, Diane; Zhang, Pengbo; Girardin, Stephen E.; Hollmann, Markus W.; Weber, Nina C.; Houten, Sander M.; van Weeghel, Michel; Kibbey, Richard G.; Zuurbier, Coert J. (Frontiers in Immunology, 2020)
Background: NOD-like receptors (NLR) are intracellular sensors of the innate immune system, with the NLRP3 being a pro-inflammatory member that modulates cardiac ischemia-reperfusion injury (IRI) and metabolism. No information is available on a possible role of anti-inflammatory NLRs on IRI and metabolism in the intact heart. Here we hypothesize that the constitutively expressed, anti-inflammatory mitochondrial NLRX1, affects IRI and metabolism of the isolated mouse heart. Methods: Isolated C57Bl/6J and NLRX1 knock-out (KO) mouse hearts were perfused with a physiological mixture of the essential substrates (lactate, glucose, pyruvate, fatty acid, glutamine) and insulin. For the IRI studies, hearts were subjected to either mild (20 min) or severe (35 min) ischemia and IRI was determined at 60 min reperfusion. Inflammatory mediators (IL-6, TNFα) and survival pathways (mito-HKII, p-Akt, p-AMPK, p-STAT3) were analyzed at 5 min of reperfusion. For the metabolism studies, hearts were perfused for 35 min with either 5.5 mM 13C-glucose or 0.4 mM 13C-palmitate under normoxic conditions, followed by LC-MS analysis and integrated, stepwise, mass-isotopomeric flux analysis (MIMOSA). Results: NLRX1 KO significantly increased IRI (infarct size from 63% to 73%, end-diastolic pressure from 59 mmHg to 75 mmHg, and rate-pressure-product recovery from 15% to 6%), following severe, but not mild, ischemia. The increased IRI in NLRX1 KO hearts was associated with depressed Akt signaling at early reperfusion; other survival pathways or inflammatory parameters were not affected. Metabolically, NLRX1 KO hearts displayed increased lactate production and glucose oxidation relative to fatty acid oxidation, associated with increased pyruvate dehydrogenase flux and 10% higher cardiac oxygen consumption. Conclusion: Deletion of the mitochondrially-located NOD-like sensor NLRX1 exacerbates severe cardiac IR injury, possibly through impaired Akt signaling, and increases cardiac glucose metabolism.